2002
DOI: 10.1523/jneurosci.22-07-02963.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activity Patterns in a Model for the Subthalamopallidal Network of the Basal Ganglia

Abstract: Based on recent experimental data, we have developed a conductance-based computational network model of the subthalamic nucleus and the external segment of the globus pallidus in the indirect pathway of the basal ganglia. Computer simulations and analysis of this model illuminate the roles of the coupling architecture of the network, and associated synaptic conductances, in modulating the activity patterns displayed by this network. Depending on the relationships of these coupling parameters, the network can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
729
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 643 publications
(787 citation statements)
references
References 51 publications
22
729
0
4
Order By: Relevance
“…These studies compare firing before HFS with that after HFS, however; thus, they do not establish how firing changes during HFS. Indeed, it is quite possible that after a period of sustained, high-frequency STN firing, STN activity will be suppressed by the activation of a calcium-gated potassium afterhyperpolarization current (Bevan et al, 1999(Bevan et al, , 2000Terman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies compare firing before HFS with that after HFS, however; thus, they do not establish how firing changes during HFS. Indeed, it is quite possible that after a period of sustained, high-frequency STN firing, STN activity will be suppressed by the activation of a calcium-gated potassium afterhyperpolarization current (Bevan et al, 1999(Bevan et al, , 2000Terman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have pointed out that the pattern of neuronal activity, not just the rate, may be important (Bergman et al, 1994;Nini et al, 1995;Magnin et al, 2000;Montgomery et al, 2000;Obeso et al, 2000;Raz et al, 2000;Brown et al, 2001;Terman et al, 2001Terman et al, , 2002. In particular, numerous experimental studies have demonstrated that neurons within both the STN and GPi show an increased level of synchrony and bursting activity during parkinsonian states (Bergman et al, 1994;Nini et al, 1995;Magnin et al, 2000;Raz et al, 2000;Brown et al, 2001).…”
Section: The Goal Of This Paper Is To Demonstrate With a Computationmentioning
confidence: 99%
See 3 more Smart Citations